Protect Indigenous peoples from COVID-19 (2020)
As coronavirus disease 2019 (COVID-19) spreads through Brazil, President Jair Bolsonaro has repeatedly denied the severity of the pandemic and broadcasted misleading information and mixed messages about how to respond, advocating for hydroxychloroquine use and the end of the country's quarantine